Emotion the basics - Brady, Michael 1965- (The basics, 2019)
What are emotions? Why are emotions important in our lives? Emotion: The Basics answers these questions, and in doing so provides accounts of the nature and value of particular emotions that are central to human existence.The overarching message is that our lives, both individual and social, would be significantly impoverished without the emotions.